From soul to mind : the emergence of psychology from Erasmus Darwin to William James - Reed, Edward (Edward S.) (Yale University Press, 1997)
Early in the nineteenth century, psychology was considered a science of the soul; by the end of the century, it had abandoned the soul to become a science of the mind, says Edward Reed. In this lively and original account of psychology's formative years, Reed relates the failures and successes of the attempts of nineteenth-century thinkers and practitionersincluding philosophers, theologians, medical workers, mesmerists, and even poets - to make psychology into a science. From Soul to Mind introduces a cast that includes not only well-known scientists and philosophers (Kant, Reid, Darwin, James) but also figures important in their time who are largely forgotten today (R.H. Lotze in Germany, G.H. Lewes in Britain) and literary notables (Mary Shelley, E.T.A. Hoffmann, Edgar Allan Poe). Countering the widespread belief that psychology is the offspring of philosophy, Reed contends that modern philosophy arose when academic philosophers sought to distinguish themselves from psychologists.
Keywords: Psychology -- History -- 19th century.; Psychology -- history; History, 19th Century; Psychologie -- Histoire -- 19e siècle.; Médecine -- Histoire -- 19e siècle.; PSYCHOLOGY -- History.; PSYCHOLOGY -- General.; Psychology; 1800-1899; History